Possibilities of Analytical Signal Usage in Numerical Demodulator MSK (Advances in Military Technology, 2022)
The article deals with applications of a DSP (Digital Signal Processor) in the MSK (FSK) demodulators. It describes simplified method of numerical processing of analytical signal. By simulation procedures it features achieved results and show possible applications.
Keywords: Engineer; engineer support; combat support engineering; close support engineering; force support engineering